Syncretic resilience: navigating climate challenges through the lens of religious syncretism in the Indian Sundarbans - Misra, Sayari (Culture and religion, 2024)
Climate change has intensified the frequency and severity of cyclones in the Indian Sundarbans Delta (ISD), resulting in significant human, economic, and environmental losses. In response to these challenges, this paper introduces ‘syncretic resilience’ as a novel approach to perceiving climate resilience in the Sundarbans. Syncretic resilience integrates diverse cultural, religious, and social practices into a unified belief system, promoting social cohesion, collective action, and sustainable environmental practices. It underscores the importance of indigenous faith in fostering environmental stewardship and resilience, which is crucial for addressing the ecological complexities of the region. Unlike conventional resilience frameworks focused solely on technological or economic solutions, syncretic resilience leverages an eco-religious approach that emphasises the collaborative integration of social and environmental resilience. It harnesses community strengths and collective faith to enhance adaptive capacity and sustainable resource management. This study explores how syncretic resilience, rooted in the fusion of Hindu, Muslim, and Indigenous traditions with reverence for Bonbibi (goddess of the forest), shapes a moral and collective belief system. It guides communities in maintaining ecological harmony, managing resources sustainably, and confronting climate change and environmental uncertainties effectively.